IMPROVING OF JUNIOR HIGH SCHOOL SCIENCE TEACHERS COMPETENCY THROUGH LESSON STUDY - Kusairi, Sentot; Khusaini, Khusaini; Sujito, Sujito; Ananingtyas, Ratika Sekar Ajeng; Irawan, Ivan Danar Aditya; Faizah, Revnika (Jurnal Pendidikan Matematika dan IPA, 2026)
This study aims to improve the competence of junior high school science teachers through Lesson Study activities and the development of scientific articles. Participatory Action Research (PAR) was chosen as the research method. The study involved 17 science teachers who were members of the Malang City Science Teacher Working Group (MGMP IPA). The teachers carried out lesson study in groups with three cycles of plan, do, see, and reflect. Each group designed, implemented, observed, and reflected on the learning process during the three cycles. Data was obtained through observation and questionnaires to identify the competencies of science teachers. The results showed that the implementation of Lesson Study was able to improve teachers' understanding of the concepts and objectives of lesson study, observation skills, and the ability to analyze learning outcomes. Teachers also had a good knowledge of formative assessment in learning. The integration of Lesson Study followed by the development of scientific articles proved to be an effective strategy for improving teacher competence. The involvement of teachers in this research also created a professional learning culture oriented towards improving the quality of science learning in schools.